Investigation the origin and mechanical properties of unusual rigid diamond-like net analogues in manganese tetraboride. (December 2019) - Ma, Shuailing; Bao, Kuo; Tao, Qiang; Huang, Yanping; Xu, Chunhong; Li, Li; Feng, Xiaokang; Zhao, Xingbin; Zhu, Pinwen; Cui, Tian
Abstract: Higher boron concentration is generally recognized as the most direct method to improve the hardness of transition metal borides. Here, we report the synthesis of manganese tetraboride, a recently proposed superhard candidate, by high pressure and high temperature solid state reaction. Hardness measurement of MnB4 yields an asymptotic hardness value of 20.1 GPa. The measured asymptotic hardness value of MnB4 is far higher than that of low boron concentration manganese borides counterparts. On the basis the results of XPS and first principle calculations, the stabilization of this three-dimensional diamond-like boron net analogue is intimately related to the fact that B − ions are electronic isostructure to the carbon atoms in diamond. In addition, the atomic radius of transition metals, RTM, is relevant to the formation of B24 and B12 boron cages in transition metal dodecaborides and tetraborides, respectively. Given the crystal structure and bond configuration, its high hardness originates from its diamond-like boron net analogues frameworks which indicate its strong covalent feature. Graphical abstract: Unlabelled Image Highlights: Boron-rich transition metal tetraboride with three-dimensional boron cages was fabricated by high pressure and high temperature method. The hardness value of MnB4 is far higher than that of low boron concentration manganese borides counterparts because of its diamond-like boron net analogues frameworks. Three-dimensional diamond-like boron net analogue is intimately related to the fact that B - ions are electronic isostructure to the carbon atoms in diamond Transition metal with large RTM adopts B24 boron cages in dodecaborides and transition metal with small RTM will crystallize in B12 boron cages in tetraborides.